POLA KELOLA WAKAF DALAM UPAYA PEMBERDAYAAN EKONOMI BERBASIS PESANTREN (Studi Wakaf Pertanian Ubi pada Lembaga Wakaf Ansor) - ISNAINI QURROTI A’YUNI ; Ajeng Wahyu Puspitasari, SE. MA (Ilmu Ekonomi FEB - UB, 2018)
This study aims to find out how to manage waqf through agriculture in an effort to pesantren-based economic empowerment carried out by Ansor Waqf Institutions as nazhir waqf. Qualitative analysis with a study approach in Indonesian and the environmental language used in the Darul Ilmi wal 'Amal Islamic Boarding School. Find out there are three patterns that explain the flow of the collaboration between institutions and Islamic boarding schools, management patterns during the planting period, and post-harvest management patterns. In each pattern there is a similar role to that which occurs during the planting period and also the management of income that replaces the pesantren to support the development of santri education. How is it possible to see online what is happening in the right form. Keywords: Waqf, Management Patterns, Economic Empowerment.